Caliphate and the Ecological Crisis: A Thematic Tafsir Analysis of the Phenomenon of Deforestation - Reza Prayogo; Mardian Idris Harahap (IJoIS: Indonesian Journal of Islamic Studies, 2026)
The current ecological crisis, particularly deforestation, is not solely a technical or environmental issue but is deeply connected to human values, moral awareness, and perceptions of nature. In Islamic teachings, the concept of *khalifah* (stewardship) offers ethical guidance regarding the relationship between humans and the environment. However, this concept is often confined to theological discourse and is rarely linked to real-world environmental problems and human behavior. This study aims to reinterpret Qur’anic teachings on *khalifah* and the prohibition of *fasād fī al-arḍ* (corruption on earth) in relation to contemporary ecological crises, especially deforestation in Indonesia, so that these teachings can be practically implemented rather than remaining theoretical. This research employs a qualitative approach with a library research method, utilizing primary sources such as the Qur’an, classical and contemporary tafsir, scholarly books, and scientific articles on ecology and stewardship. The study applies a thematic (*tafsir maudhu‘i*) approach, supported by comparative (*muqāran*) analysis, to examine key verses related to environmental ethics, including QS. Al-A‘raf [7]:56, QS. Ar-Rum [30]:41, QS. Al-Baqarah [2]:11–12, and QS. Al-Baqarah [2]:205. The findings reveal three main points. First, the Qur’an presents a comprehensive and systematic framework of environmental ethics. Second, it not only provides normative guidance but also highlights that environmental destruction is a direct consequence of human actions. Third, the root cause of ecological damage, from a Qur’anic perspective, lies in the internal human dimension, particularly moral crisis, hypocrisy, and distorted consciousness. These findings emphasize the urgency of integrating religious values into environmental practices to address ecological degradation effectively.